L’effacement des Autochtones et du colonialisme de l’école des colons : analyse de la définition du personnel enseignant non autochtone au Québec des rapports entre Autochtones et non-Autochtones - St-Pierre, Xavier; Hirsch, Sivane (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
In this article, I focus on the social relations related to settler colonialism (Coulthard, 2018; Wolfe, 2006) in a non-Indigenous school context. The objective pursued in this article is to analyze how the logic of erasure of settler colonialism (Veracini, 2011) manifests itself in the “settler school”. Using an interactionist approach (Blumer, 1962), I describe the “definition of the situation” of the relationship between Indigenous and non-Indigenous people through the discourse of non-Indigenous teachers in a colonial context. Thematic analysis of interviews with six high school teachers in various subjects allows us to identify that the relationship between Indigenous and non-Indigenous is defined as external to the school situation of non-Indigenous in a logic of erasure of colonialism and Indigenous people.